2009
DOI: 10.1007/s00330-009-1602-4
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and reliability of language laterality assessment with a free reversed association task—a fMRI study

Abstract: 'Free reversed association' is a sensitive and reliable task for the determination of individual language lateralization. This suggests that the task may be used in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 53 publications
4
28
0
1
Order By: Relevance
“…The test‐retest reproducibility of the adaptive semantic matching paradigm was good, with a mean Dice coefficient of similarity of 0.66 with our a priori analysis parameter set, and even higher Dice coefficients with other parameter sets. This compares favorably to all other reliability coefficients that have been reported for language mapping paradigms (Billingsley‐Marshall, Simos, & Papanicolaou, ; Brannen et al, ; Fernández et al, ; Fesl et al, ; Gross & Binder, ; Harrington et al, ; Maldjian et al, ; Rau et al, ; Rutten et al, ; see Wilson et al, for review); to our knowledge, the highest Dice coefficient previously reported for a paradigm with reasonable validity is 0.61 (Fesl et al, ), and participants in that study were neurologically normal. Other investigations of language mapping reliability in aphasia have used metrics such as the voxelwise intraclass correlation coefficients that do not provide an overall assessment of reliability (Eaton et al, ; Meltzer et al, ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The test‐retest reproducibility of the adaptive semantic matching paradigm was good, with a mean Dice coefficient of similarity of 0.66 with our a priori analysis parameter set, and even higher Dice coefficients with other parameter sets. This compares favorably to all other reliability coefficients that have been reported for language mapping paradigms (Billingsley‐Marshall, Simos, & Papanicolaou, ; Brannen et al, ; Fernández et al, ; Fesl et al, ; Gross & Binder, ; Harrington et al, ; Maldjian et al, ; Rau et al, ; Rutten et al, ; see Wilson et al, for review); to our knowledge, the highest Dice coefficient previously reported for a paradigm with reasonable validity is 0.61 (Fesl et al, ), and participants in that study were neurologically normal. Other investigations of language mapping reliability in aphasia have used metrics such as the voxelwise intraclass correlation coefficients that do not provide an overall assessment of reliability (Eaton et al, ; Meltzer et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…V overlap /(V 1 + V 2 ) where V overlap is the number of overlapping voxels, V 1 is the number of voxels activated in the first scan, and V 2 is the number of voxels activated in the second scan (Figure c). The advantages of the Dice coefficient are that it is easy to interpret (Bennett & Miller, ), is widely used (e.g., Fernández et al, ; Fesl et al, ; Gross & Binder, ; Harrington et al, ; Rutten et al, ), can be calculated in any individual without reference to a group (Bennett & Miller, ); and yields a single metric of overall activation similarity encompassing all brain regions under consideration (Wilson et al, ). In these last two respects, the Dice coefficient is more useful than the intraclass correlation coefficient, another metric sometimes used in research on language mapping paradigms (Fernández et al, ; Eaton et al, ; Meltzer et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They advocated plotting the LI as a function of the number of active voxels, similar to threshold dependent curves; these curves are however tighter and more stable. Furthermore, Fesl et al (2010) reported improved reliability of LI measurement when using this variable threshold method as opposed to a single fixed threshold. However, this approach does not remove the need for arbitrary decisions, since a ‘reasonable’ fixed number of active voxels must be decided on.…”
Section: Resultsmentioning
confidence: 97%
“…One such method involves choosing that threshold which yields a fixed number of active voxels for each individual participant (Knecht et al, 2003; Jansen et al, 2006; Abbott et al, 2010; Fesl et al, 2010). Using simulated data, Abbott et al (2010) demonstrated that thresholding at a fixed number of voxels was more robust against variability in signal strength than the standard thresholding method.…”
Section: Resultsmentioning
confidence: 99%